Calibration and validation of hydrodynamic, salt and heat transport models for Ria de Aveiro lagoon (Portugal) - Dias, J. M. (2004)
Ria deAveiro is a very complex shallow water coastal lagoon located on the northwest of Portugal. Important issues would be left unanswered without a good understanding of hydrodynamic and transport processes occurring in the lagoon. Calibration and validation of hydrodynamic, salt and heat transport models for Ria de Aveiro lagoon are presented. The calibration of the hydrodynamic model was performed adjusting the bottom friction coefficient, through the comparison between measured and predicted time series of sea surface elevation for 22 stations. Harmonic analysis was performed in order to evaluate the model's accuracy. To validate the hydrodynamic model measured and predicted SSE values were compared for 11 stations, as well as main flow direction velocities for 10 stations. The salt and heat transport models were calibrated comparing measured and predicted time series of salinity and water temperature for 7 stations, and the RMS of the difference between the series was determined. These models were validated comparing the model results with an independent field data set. The hydrodynamic and the salt and heat transport models for Ria de Aveiro were successfully calibrated and validated. They reproduce accurately the barotropic flows and can therefore adequately represent the salt and heat transport and the heat transfer processes occurring in Ria deAveiro.